AN An Analysis of Flouting Maxims in the Second American Presidential Debate - Rakhmasari, Dwi Lia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Language becomes the prior instrument in communicating ideas, feeling, or opinions. In real communication, those four maxims are not always being fulfilled by the speakers. When the speakers do not fulfil the maxim in the communication, means that they flout the maxim. There are many flouting maxims found in the real communication. Debate can be an interesting object for seeing that phenomenon. One of many famous debates is American presidential debate in 2008, especially the second part of the debate. In this ocassion, there are many guests who had never voted in the election before. The aim of this study is to investigate the flouted utterances in the second American presidential debate and to answer the question about how the the two presidential candidates flouted the maxims. This study is conducted by using qualitative approach since the writers analyze about the flouted utterances in the second American presidential debate. The script is taken from the website www.debates.org. the two presidential candidates performed flouting maxim of quantity, flouting maxim of relevance, and flouting maxim of manner. Key words: debate, flouting maxim, good communication